2003
DOI: 10.1891/vivi.2003.18.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Psychological, Physical, and Sexual Aggression Among College Students Using the Revised Conflict Tactics Scales

Abstract: In response to criticisms of the Conflict Tactics Scales, Straus revised the original scale to include sexual aggression and injury. The purpose of the present study was to use this new scale to replicate and expand existing knowledge of psychological, physical, and sexual aggression in dating relationships. Four-hundred-eighty-one college students completed the Revised Conflict Tactics Scales. As expected, females reported perpetrating more psychological aggression than males; there were no gender differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
170
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(207 citation statements)
references
References 26 publications
31
170
2
4
Order By: Relevance
“…Johnson added this category to his existing typology, along with "violent resistance," to allow the behavior of both partners to be included, moving from an individual to dyadic typology. This finding supports several studies that have demonstrated the damaging physical and psychological effects that men suffer when they are victims of an intimate terrorist partner (e.g., Hines & Saudino, 2003;Hines et al, 2007;Hines & Douglas, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Johnson added this category to his existing typology, along with "violent resistance," to allow the behavior of both partners to be included, moving from an individual to dyadic typology. This finding supports several studies that have demonstrated the damaging physical and psychological effects that men suffer when they are victims of an intimate terrorist partner (e.g., Hines & Saudino, 2003;Hines et al, 2007;Hines & Douglas, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Other studies indicate that control and controlling aggression are characteristic of both sexes (Dutton & Nicholls, 2005;Felson & Outlaw, 2007;Graham-Kevan, 2007;GrahamKevan & Archer, 2009). Furthermore, Hines (e.g., Hines & Saudino, 2003;Hines, Brown, & Dunning, 2007;Hines & Douglas, 2010) has described the severe physical and psychological effects that male victims of IPV suffer.…”
Section: Introductionmentioning
confidence: 99%
“…The Conflict Tactics Scale-Revised was employed by Hines and Saudino (2003) in their study which found that 86% of the women and 82% of the men informed perpetration of psychological aggression in their partner relations. The samples comprised of college students and based on the findings of their study, they defined psychological aggression as swearing, shouting and yelling at partner.…”
Section: Higher Psychological Aggression In Women Compared In To Menmentioning
confidence: 99%
“…Prior research has not found that the likelihood of reporting physical abuse is affected by the victim's gender (Hines & Saudino, 2003). Straus & Ramirez (2007) report that women were significantly more likely to be seriously injured than men in cases of intimate partner physical abuse.…”
Section: Discussionmentioning
confidence: 99%
“…More common is the presence of psychological abuse, with some studies reporting up to 80% of college aged couples experiencing this type of victimization (Avant, Swopes, Davis, & Elhai, 2011;Cercone, Beach, & Arias, 2005;Harned, 2001;Hines & Saudino, 2003). Although male and female college students report similar rates of physical and psychological abuse by a partner, female college students report sexual assault at higher rates than male college students.…”
Section: Intimate Partner Violencementioning
confidence: 99%